Management of Education and Training Centers in Improving Vocational School Teacher Competence - Finsa Muhamad Pratama; Danang Ari Wibowo; Anita Fitri Rahmawati; Lilis Suwandari (Al-Qalam Institue, 2025)
This study aims to analyze the management of education and training centers in improving vocational school teachers’ competencies. Using a qualitative descriptive approach, data were collected through in-depth interviews with training center managers and vocational school teachers, direct observation of training activities, and document analysis, including training modules and evaluation reports. The key findings indicate that effective management of training centers is characterized by strategic planning based on training needs analysis, the implementation of professional development programs with industry collaboration, and the application of both formative and summative evaluation systems. The study highlights the importance of aligning training management with ongoing curriculum developments, technological advancements, and industrial requirements. The novelty of this research lies in its integrated approach that links managerial strategies directly with measurable improvements in teacher performance and learning outcomes in vocational education. The results show that adaptive and responsive training systems, strengthened by sustainable school-industry partnerships, are essential to guarantee continuous competence development among vocational teachers. The study recommends further research on the implementation of more flexible and scalable digital-based or hybrid training models to reach a broader range of educators across different regions and sectors.